Biological description of commercial fish populations of the Tobol river (Experimental biology, 2020)
The Tobol river is an important national economic reservoir and is used for various purposes, including fishing. The material was collected as a result of field trips in 2019. 6 stations on the Tobol river were surveyed. The current state of fish populations has been studied. The total number of fish species in the Tobol river was 13 species. Of the 13 species, only 11 are commercial, and only 4 species have a high number and wide distribution: roach, common perch, common pike and bream. All fish species that live in the Tobol river are found throughout its length, so the composition of the commercial ichthyofauna is imilar in all, except for certain fishing areas. The state of populations of all mass species is satisfactory. The analysis of stability indicators (gender and age structure of populations) showed mainly the excess of replenishment over the main commercial herd. In the Tobol river, the maximum life expectancy of roach and common pike was 5+ years, common perch and bream 7+ years. It is recommended to use the stocks of common pike of the Tobol river for the purpose of reproduction of fish resources (including stocking in other reservoirs), and also pre-allocate on the river Tobol 2 sites for the organization of sports and Amateur fishing.Key words: fish, river, Tobol, species, ichthyofauna, population, size structure, age composition, fertility.